Prevalence, Clinico- Pathology And Control Of Coccidiosis In Broiler Chicken - Gigi George A (Department of Parasitology, College of Veterinary and Animal Sciences, 1997)
An investigation was carried out with an objective to findout the prevalence, clinicopathology and control of coccidiosis in broiler chicken. The prevalence of coccidiosis in broiler chicken by viscera examination was 21.13% and by the examination of faecal sample from different broiler farms was 10.65%. The highest prevalence of coccidiosis was during the warm wet climate (September to November). There was prevalence of three species of Eimeria namely E. tenella (72%), E. necatrix (36%) and E. maxima (1.33%) and mixed infection with E. tenella and E. necatrix in 9.33% cases. Haematological studies revealed increase in erythrocyte sedimentation rate and total leucocyte count than the control and a decrease in the values for PCV, Hb content and total red blood cell count. Histopathological observations revealed proliferation of goblet cells, moderate mononuclear cell infiltration, degeneration and desquamation of caecal mucous membrane and haemorrhage at different depths of the intestinal wall caused by the rupture of the large second generation schizonts. Among the three anticoccidials evaluated salinomycin was the best drug based on the mean weekly body weight, mean